REVIVING BRASÍLIA THROUGH ANALYZING HISTORICAL AERIAL PHOTOGRAPHS - Garcia, Leandro Faleiros; Rego, Luiz Felipe Siqueira Marques; Pessoa, Guilherme Gomes; Cicereli, Rejane Ennes; Neumann, Marina Rolim Bilich; Oliveira, Elton Souza; Maia, Dayana; de Almeida, Tati; Roig, Henrique Llacer (Ra'e Ga: o Espaço Geográfico em Análise, 2024)
This study presents an optimized method for processing and retrieving digital data from 1950s aerial photographs of the Plano Piloto area in Brasília. In analogous contexts, internal orientation parameters are often unavailable, and external orientation parameters must be obtained through non-standard approaches, as the identification and geolocation of control points in the field becomes impractical in substantially altered landscapes. Nevertheless, advancements in computer vision techniques, integrated into modern photogrammetry software such as Agisoft Metashape, provide a viable solution for mapping historical analog aerial photographs. The software successfully processed 156 aerial photographs, using 17 control points, yielding a historical orthoimage and a digital surface model with medium-scale accuracy. The generated model enabled precise identification of key features, including vegetation cover, land use, and terrain characteristics, providing valuable insights for the analysis of land occupation dynamics in the study area. The proposed methodology exhibits substantial potential for replication in similar cases, establishing a robust framework for the processing of historical aerial imagery.